A stainless steel seamless pipe with gradient nano-twin structure and a preparation process thereof

CN122999735APending Publication Date: 2026-10-30JIANGYIN SOUTH STAINLESS STEEL PIPES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611468942.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]针对现有技术中冷轧不锈钢管强度与塑性难以兼顾、梯度结构制备局限于表层、以及常规不锈钢中纳米孪晶梯度调控手段缺乏的问题,本发明提供一种具有梯度纳米孪晶结构的不锈钢无缝管及其制备工艺,旨在通过多道次旋转冷轧与程控间歇式深冷处理的协同作用,在不显著牺牲延伸率的前提下大幅提高管材的屈服强度,并获得壁厚方向上纳米孪晶体积分数连续梯度分布的管材

Benefits of technology

[0033]本发明的一种具有梯度纳米孪晶结构的不锈钢无缝管及其制备工艺跟现有技术相比具有的优点在于,

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a stainless steel seamless pipe with gradient nano twin crystal structure and a preparation process thereof. The process comprises the following steps: selecting a solid solution austenitic stainless steel pipe blank with specific components; performing multi-pass rotary cold rolling, with the pipe rotating by 80-100 degrees between adjacent passes; performing cryogenic treatment when the total cross-section reduction rate reaches 30-40% and 55-65%; performing gradient annealing in a nitrogen-argon mixed atmosphere; and performing rotary shot peening nanocrystallization treatment on the inner wall. The volume fraction of nano twin crystals in the obtained pipe gradually decreases from 45-65% on the inner wall to 5-15% on the outer wall in the wall thickness direction, the yield strength reaches 680-850 MPa, and the elongation is kept at 18-25%, so that the strength and plasticity are synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal material processing technology, specifically to a seamless stainless steel tube with a gradient nanotwin structure and its manufacturing process, and more particularly to a method for controlling the nanotwin gradient distribution in the tube wall thickness direction by combining multi-pass rotary cold rolling with programmable intermittent deep cryogenic treatment. Background Technology

[0002] Austenitic stainless steel is widely used in chemical equipment, marine engineering, medical devices, and nuclear power equipment due to its excellent corrosion resistance, good formability, and weldability. However, the yield strength of conventional solution-treated austenitic stainless steel is typically only 200-350 MPa, which limits its application range under high pressure and high load conditions. Taking high-pressure heat exchange tubes in the chemical industry as an example, the tubes must simultaneously withstand the high pressure of the internal medium and the load of the external structure, making the requirements for the synergy between strength and plasticity extremely stringent.

[0003] To improve the strength of austenitic stainless steel, existing technologies typically employ cold working deformation methods such as cold rolling and cold drawing. Cold rolling deformation increases strength by introducing high-density dislocations and deformation twins; however, when the reduction of section exceeds 60%, the elongation of the tube drops sharply to below 5%, exhibiting a significant strength-plasticity inversion phenomenon. Furthermore, during conventional cold rolling, the deformation of the tube along the wall thickness tends to become uniform, making it difficult to form a controllable microstructure gradient.

[0004] Gradient structure metallic materials have attracted widespread attention due to their ability to effectively alleviate the contradiction between strength and plasticity. Gradient structures are achieved by creating a continuous microstructural gradient from the surface to the core within the material, utilizing deformation coordination between different regions and heterogeneous deformation-induced strengthening to significantly improve strength while maintaining high plasticity. However, existing gradient structure fabrication techniques are mostly limited to the surface layer within a few hundred micrometers, such as surface mechanical grinding and surface mechanical rolling, making it difficult to construct an integral gradient structure across the entire wall thickness of the tube.

[0005] In the field of pipe forming, high-strength spinning technology has been used to prepare high-manganese steel pipes with a gradient nanotwinned structure. Studies have shown that the non-uniform deformation characteristics of high-strength spinning along the wall thickness direction can cause the twinning probability to increase gradually from the inner layer to the outer layer, with the twin boundary spacing decreasing from 154.5 nm to 47.3 nm and the hardness continuously increasing from 3.32 GPa to 5.45 GPa. However, this technology depends on the specific composition design of high-manganese steel, and its twinning behavior is highly sensitive to strain changes. Its applicability to conventional austenitic stainless steels such as 304L and 316L is limited, and high-strength spinning has poor adaptability to pipe size and wall thickness.

[0006] Cyclic torsional deformation has also been used to introduce gradient dislocation structures in tubular 321 stainless steel. By controlling the amplitude of the torsional angle, the cumulative shear strain is made to exhibit a gradient distribution along the radial direction, resulting in a continuously increasing microhardness from the inner wall to the outer wall. However, torsional deformation is difficult to guarantee axial uniformity in tubular materials with large aspect ratios, and the resulting gradient structure is dominated by dislocation cells with a limited number of nanotwin integrals, resulting in a strengthening effect that is not as good as that of gradient nanotwin structures.

[0007] The application of cryogenic treatment in steel materials mainly focuses on the stabilization of residual austenite and the improvement of dimensional stability. Research on combining cryogenic treatment as a microstructure control method with cold rolling deformation to construct a nanotwin gradient distribution remains lacking. In particular, how to achieve gradient control of the nanotwin integral number in the wall thickness direction in conventional austenitic stainless steel through precise control of process parameters, while avoiding plasticity deterioration caused by excessive martensitic transformation, is an unsolved technical challenge. Summary of the Invention

[0008] To address the problems in existing technologies, such as the difficulty in balancing strength and plasticity in cold-rolled stainless steel tubes, the limitation of gradient structure preparation to the surface layer, and the lack of methods for controlling the nanotwin gradient in conventional stainless steel, this invention provides a seamless stainless steel tube with a gradient nanotwin structure and its preparation process. The aim is to significantly improve the yield strength of the tube without significantly sacrificing elongation by using the synergistic effect of multi-pass rotary cold rolling and programmable intermittent deep cryogenic treatment, and to obtain a tube with a continuous gradient distribution of nanotwin integral numbers in the wall thickness direction.

[0009] The first objective of this invention is to provide a process for manufacturing seamless stainless steel tubes with a gradient nanotwinned structure, comprising the following steps:

[0010] Includes the following steps:

[0011] S1. Provide a solution-treated austenitic stainless steel seamless tube blank, wherein the tube blank has a wall thickness of 3.0~6.0mm, an outer diameter of 20~40mm, and its chemical composition by weight percentage is: C≤0.03%, Si≤1.0%, Mn8.0-12.0%, P≤0.045%, S≤0.030%, Cr16.0~19.0%, Ni6.0~9.0%, N0.15~0.35%, with the balance being Fe and unavoidable impurities;

[0012] The wall thickness of the tube blank is selected as 3.0~6.0 mm. This wall thickness range ensures sufficient strain gradient in the wall thickness direction during subsequent cold rolling, and also facilitates the uniform nano-sizing of the inner wall through rotary shot peening. When the wall thickness is too thin (less than 3.0 mm), the strain gradient during cold rolling is insufficient to form a significant nanotwin gradient distribution; when the wall thickness is too thick (greater than 6.0 mm), the rolling force required for cold rolling increases significantly, and the thermal stress gradient of cryogenic treatment is difficult to penetrate the entire wall thickness.

[0013] In the chemical composition, the Mn content, controlled at 8.0–12.0%, serves to stabilize the austenite structure and reduce stacking fault energy. Lower stacking fault energy promotes the nucleation and growth of deformation twins, making the formation of nanotwins more sensitive to changes in cold rolling strain. When the Mn content is below 8.0%, the stacking fault energy is too high, making twin nucleation difficult; when the Mn content is above 12.0%, excessive ε-martensite may form, impairing corrosion resistance. The N content, controlled at 0.15–0.35%, serves to strengthen through solid solution and further stabilize the austenite. The Cr and Ni contents are adjusted according to conventional 304L or 316L systems to ensure basic corrosion resistance.

[0014] S2. The tube blank is subjected to multi-pass cold rolling, with a cross-sectional reduction rate of 12% to 18% per pass. The tube is rotated 80° to 100° around its axis between adjacent passes, and the total cross-sectional reduction rate is 70% to 85%.

[0015] The selection of the rotation angle plays a crucial role. In conventional cold rolling, the stress state of the tube is roughly the same along the circumference during each rolling pass, and the strain distribution is relatively uniform. When the tube is rotated 90° around the axis (i.e., the optimal value within the range of 80°-100°), the superposition of the shear strain generated in a specific direction in the previous pass and the strain generated in the same direction in the subsequent pass changes, causing a periodic reorientation of the cumulative shear strain distribution in the tube wall thickness direction. This periodic strain reorientation promotes the differential accumulation of deformation degrees between different regions in the wall thickness direction, laying the strain foundation for the subsequent formation of a nanotwin gradient distribution.

[0016] The reduction in cross-section per pass is controlled within the range of 12% to 18%. Below 12%, the plastic strain introduced in a single pass is insufficient to activate twin nucleation; above 18%, the deformation in a single pass is too large, increasing the risk of microcracks on the pipe surface. The total reduction in cross-section is controlled within the range of 70% to 85%. Below 70%, the integral number of nanotwins is insufficient, resulting in limited strengthening effect; above 85%, the volume fraction of martensite phase transformation increases significantly, and the elongation decreases excessively.

[0017] S3. During the multi-pass cold rolling process, a first cryogenic treatment is performed when the total cross-sectional area reduction reaches 30%~40%, and a second cryogenic treatment is performed when the total cross-sectional area reduction reaches 55%~65%. The temperature for each cryogenic treatment is -120°C to -160°C. When the total cold rolling reduction reaches 30%~40%, a certain dislocation density and deformation twins have accumulated inside the tube, but the microstructure is still dominated by dislocation cells and a small number of twins. At this time, cryogenic treatment is performed. During the cooling process, thermal stress is generated in the tube due to the difference in the coefficient of thermal expansion. This thermal stress is superimposed on the existing cold rolling residual stress, which promotes the further refinement of dislocation cells and the densification of dislocation walls in the inner wall region (the region with relatively large strain during cold rolling). During the reheating process, some high-density dislocation regions recover, forming a microstructure state that is conducive to subsequent twin nucleation.

[0018] The second cryogenic treatment is performed when the total shrinkage rate is 55%~65%. At this time, a certain number of deformation twins have been formed inside the tube. The thermal stress gradient generated by the cryogenic treatment further refines the twins in the inner wall region, while promoting the migration of dislocations to twin boundaries in the outer wall region (the region with relatively small strain), creating conditions for the gradient growth of nanotwins in the subsequent annealing process.

[0019] The cooling rate should be controlled at 5~10°C / min. Too fast a rate will result in an excessive temperature difference between the inner and outer walls of the pipe, generating excessive thermal stress and increasing the risk of cracking. Too slow a rate will result in insufficient thermal stress gradient, making it difficult to effectively promote the evolution of dislocation structures in the inner wall region. The reheating rate should be controlled at 2-5°C / min. A slower reheating rate allows sufficient recovery time for dislocations, avoiding stress concentration caused by rapid reheating.

[0020] S4. The pipe obtained in step S3 is annealed in a nitrogen-argon mixed atmosphere at a temperature of 780-850°C. The nitrogen component in the mixed atmosphere is 15%-25%, and the total pressure inside the furnace is 0.15-0.25 MPa. The annealing temperature of 780-850°C is lower than the complete recrystallization temperature of conventional austenitic stainless steel (usually 900-1050°C), but higher than the critical temperature required for nanotwin nucleation. Within this temperature range, the deformation energy stored in the cold-rolled structure drives the recovery and partial recrystallization process, but does not lead to complete grain coarsening. The inner wall region has the most significant cold rolling strain and cryogenic treatment effect, resulting in the highest stored energy. During annealing, nanotwin nucleation and growth preferentially occur. The middle region has the second highest stored energy, resulting in a lower nanotwin component. The outer wall region has the lowest stored energy, resulting in only limited recovery and the lowest nanotwin component. Thus, a gradient distribution of nanotwin component numbers is formed along the pipe wall thickness direction.

[0021] The purpose of the nitrogen-argon mixed atmosphere is as follows: nitrogen, as an austenite stabilizing element, replenishes the nitrogen content that may be lost due to cold rolling and cryogenic treatment during the annealing process through surface nitriding, thus maintaining the stability of the austenite structure; argon, as an inert diluent gas, regulates the partial pressure of nitrogen, preventing the precipitation of nitrides caused by excessively high nitrogen partial pressure. The total pressure inside the furnace is controlled at 0.15~0.25MPa, slightly higher than atmospheric pressure, to prevent air infiltration and oxidation.

[0022] The cooling rate is controlled at 20~30°C / min, which is sufficient to suppress the excessive growth of nanotwins after annealing, while avoiding thermal stress caused by excessively rapid cooling that could lead to pipe deformation.

[0023] S5. Perform surface nano-treatment on the inner wall of the annealed pipe. The surface nano-treatment is rotary shot peening, the shot peening medium is zirconia ceramic shot with a diameter of 0.1~0.3mm, and the peening pressure is 0.3~0.5MPa.

[0024] Specifically, the multi-pass cold rolling in step S2 uses a three-roll planetary rolling mill with a rolling speed of 30~60mm / s.

[0025] Furthermore, the surface roughness Ra of the rolls in the three-roll planetary rolling mill is ≤0.4μm.

[0026] Specifically, in step S3, each cryogenic treatment process involves cooling to the cryogenic treatment temperature at a rate of 5~10°C / min, holding at that temperature for 30~60 minutes, and then warming back to room temperature at a rate of 2~5°C / min.

[0027] Specifically, in step S3, the cryogenic treatment is carried out in a liquid nitrogen vaporization atmosphere.

[0028] Specifically, in step S4, the holding time for the annealing treatment is 10-30 minutes, and the cooling rate is 20-30°C / min.

[0029] Specifically, in step S5, the rotation speed of the pipe used for rotary shot peening is 200~400 rpm, and the shot peening time is 3~8 minutes.

[0030] Specifically, step S5 is followed by steps of straightening and electropolishing the tube.

[0031] The second objective of this invention is to provide a seamless stainless steel tube with a gradient nanotwin structure prepared by the above-mentioned process, wherein the nanotwin integral percentage decreases in a gradient from the inner wall to the outer wall along the tube wall thickness direction: 45%~65% in the inner wall region, 20%~40% in the middle region, and 5%~15% in the outer wall region.

[0032] Furthermore, the pipe has a yield strength of 680~850MPa, an elongation of 18%~25%, and a grain size of 20~80nm in the inner wall surface layer depth range of 0~50μm.

[0033] The advantages of the stainless steel seamless tube with a gradient nanotwin structure and its preparation process of the present invention compared with the prior art are as follows:

[0034] (1) Significant strength improvement: The yield strength of the pipe reaches 680~850MPa, which is about 2~3 times higher than that of the solid solution pipe of the same composition (yield strength of about 250~320MPa). The strength improvement comes from the effective obstruction of dislocation movement by nanotwin boundaries and the heterogeneous deformation-induced strengthening effect generated by the gradient structure;

[0035] (2) Good plasticity retention: The elongation of the tube is maintained at 18%~25%, which is much higher than the elongation of uniform cold-rolled tubes at the same strength level (usually less than 8%). The plasticity retention is attributed to the strain delocalization effect in the gradient structure: the softer outer wall region undergoes plastic deformation first, and the strain is distributed to the harder inner wall region through interface transfer, which delays the strain localization and crack initiation in the nanotwin layer of the inner wall region;

[0036] (3) Strength-plasticity synergistic optimization: The gradient nanotwin structure enables the strength-plasticity product (yield strength × elongation) of the tube to reach 12240~21250MPa·%, which is significantly better than that of uniform cold-rolled tube (the strength-plasticity product is usually less than 5000MPa·%).

[0037] (4) Additional reinforcement of the inner wall: The nano-scale treatment of the inner wall surface further enhances the hardness of the inner wall surface layer, while the continuous transition between the nanocrystalline layer and the nanotwin layer ensures the interfacial bonding strength. Detailed Implementation

[0038] The specific embodiments of the present invention will be described in further detail below.

[0039] To further illustrate the present invention, the present invention will be described in detail below with reference to embodiments and comparative examples.

[0040] Example 1

[0041] A fabrication process for a seamless stainless steel tube with a gradient nanotwin structure includes the following steps:

[0042] Tube blank preparation: Select a solution-treated austenitic stainless steel seamless tube blank with an outer diameter of 32 mm and a wall thickness of 4.5 mm. Its chemical composition by weight percentage is: C 0.025%, Si 0.65%, Mn 9.8%, P 0.032%, S 0.008%, Cr 17.5%, Ni 7.2%, N 0.22%, with the balance being Fe and unavoidable impurities. The tube blank is solution-treated at 1050°C for 30 minutes and then water-quenched.

[0043] Multi-pass rotary cold rolling: Cold rolling is performed using a three-roll planetary mill at a rolling speed of 45 mm / s, with a roll surface roughness Ra ≤ 0.3 μm. The first pass has a section reduction rate of 15%, followed by a second pass where the tube is rotated 90° around its axis, resulting in a section reduction rate of 16%. A third pass is then performed after another 90° rotation, with a section reduction rate of 15%. This process is repeated alternately, with each pass involving a 90° rotation.

[0044] First cryogenic treatment: When the cumulative total section reduction rate reaches 36%, cold rolling is suspended, and the tube is placed in a cryogenic chamber with a liquid nitrogen vaporization atmosphere. It is cooled to -140°C at a rate of 8°C / min, held at that temperature for 45 minutes, and then warmed back to room temperature (25°C) at a rate of 3°C / min.

[0045] Continue cold rolling: After reheating, continue rolling according to the above-mentioned rotary cold rolling process.

[0046] Second cryogenic treatment: When the cumulative total section reduction rate reaches 60%, cold rolling is paused again. Cool to -150°C at a rate of 6°C / min, hold for 40 minutes, and then warm to room temperature at a rate of 4°C / min.

[0047] Complete cold rolling: After reheating, continue cold rolling until the total section reduction rate is 78%. The final tube outer diameter is approximately 19.5 mm, and the wall thickness is approximately 2.1 mm.

[0048] Gradient annealing: The tube is placed in a tubular heat treatment furnace, and a mixed gas with a nitrogen component of 20% and an argon component of 80% is introduced, with a total furnace pressure of 0.20 MPa. The temperature is increased to 820°C at a rate of 10°C / min, held for 20 minutes, and then cooled to room temperature at a rate of 25°C / min.

[0049] Nano-surface treatment of the inner wall: The inner wall of the pipe is treated using a rotary shot peening system. The shot peening medium is 0.2 mm diameter zirconia ceramic shot, the blasting pressure is 0.4 MPa, the pipe rotation speed is 300 rpm, and the shot peening time is 5 minutes.

[0050] Example 2

[0051] A fabrication process for a seamless stainless steel tube with a gradient nanotwin structure includes the following steps:

[0052] Tube blank preparation: The tube blank dimensions and chemical composition are the same as in Example 1.

[0053] Multi-pass rotary cold rolling: rolling speed 35 mm / s, roll surface roughness Ra ≤ 0.4 μm. The reduction rate of cross section per pass alternates between 14% and 17%. The tube rotates 85° between adjacent passes.

[0054] First cryogenic treatment: Performed when the total shrinkage rate is 33%. Cooling rate: 7°C / min, cooling to -125°C, holding for 50 minutes, warming rate: 2.5°C / min.

[0055] Second cryogenic treatment: Performed when the total shrinkage rate is 58%. Cooling rate: 5°C / min, cooling to -155°C, holding for 55 minutes, warming rate: 3.5°C / min.

[0056] Final cold rolling: total section reduction rate 75%.

[0057] Gradient annealing: nitrogen gas integral 18%, argon gas gas integral 82%, total pressure 0.18 MPa. Annealing temperature 800°C, holding time 25 minutes. Cooling rate 22°C / min.

[0058] Inner wall shot peening: zirconia shot diameter 0.15mm, blasting pressure 0.35MPa, pipe rotation speed 250rpm, time 6 minutes.

[0059] Example 3

[0060] A fabrication process for a seamless stainless steel tube with a gradient nanotwin structure includes the following steps:

[0061] Tube blank preparation: Select a solution-treated austenitic stainless steel tube blank with an outer diameter of 28mm and a wall thickness of 3.8mm. The chemical composition by weight percentage is: C 0.028%, Si 0.72%, Mn 11.2%, P 0.028%, S 0.006%, Cr 16.8%, Ni 6.5%, N 0.28%, with the balance being Fe and unavoidable impurities.

[0062] Multi-pass rotary cold rolling: rolling speed 50 mm / s. Section reduction rate per pass is between 13% and 17%. The tube rotates 95° between adjacent passes.

[0063] First cryogenic treatment: Performed when the total shrinkage rate is 38%. Cooling rate: 9°C / min, cooling to -135°C, holding for 35 minutes, warming rate: 4.5°C / min.

[0064] Second cryogenic treatment: Performed when the total shrinkage rate reaches 63%. Cooling rate: 8°C / min, cooling to -145°C, holding for 45 minutes, warming rate: 3°C / min.

[0065] Final cold rolling: Total section reduction rate 82%.

[0066] Gradient annealing: nitrogen gas integral 22%, argon gas gas integral 78%, total pressure 0.22 MPa. Annealing temperature 840°C, holding time 15 minutes. Cooling rate 28°C / min.

[0067] Inner wall shot peening: zirconia shot diameter 0.25mm, blasting pressure 0.45MPa, pipe rotation speed 350rpm, time 4 minutes.

[0068] Example 4

[0069] A fabrication process for a seamless stainless steel tube with a gradient nanotwin structure includes the following steps:

[0070] Tube blank preparation: Select a solution-treated austenitic stainless steel seamless tube blank with an outer diameter of 36mm and a wall thickness of 5.2mm. The chemical composition by weight percentage is: C 0.022%, Si 0.58%, Mn 8.5%, P 0.035%, S 0.010%, Cr 18.2%, Ni 8.5%, N 0.18%, with the balance being Fe and unavoidable impurities.

[0071] Multi-pass rotary cold rolling: rolling speed 55 mm / s, roll surface roughness Ra ≤ 0.35 μm. Section reduction rate per pass is between 12% and 18%. The tube rotates 90° between adjacent passes.

[0072] First cryogenic treatment: Performed when the total shrinkage rate is 40%. Cooling rate: 10°C / min, cooling to -120°C, holding for 60 minutes, warming rate: 5°C / min.

[0073] Second cryogenic treatment: Performed when the total shrinkage rate reaches 65%. Cooling rate: 7°C / min, cooling to -160°C, holding for 30 minutes, warming rate: 2°C / min.

[0074] Final cold rolling: total section reduction rate 70%.

[0075] Gradient annealing: nitrogen gas integral 25%, argon gas gas integral 75%, total pressure 0.25 MPa. Annealing temperature 780°C, holding time 30 minutes. Cooling rate 20°C / min.

[0076] Inner wall shot peening: zirconia shot diameter 0.3mm, blasting pressure 0.5MPa, pipe rotation speed 200rpm, time 8 minutes.

[0077] Comparative Example 1 (without cryogenic treatment)

[0078] Except for omitting the two cryogenic treatments, the other process parameters are exactly the same as in Example 1.

[0079] Comparative Example 2 (Single Cryogenic Treatment)

[0080] Only one cryogenic treatment (-140°C, held for 45 minutes) was performed when the total cross-sectional reduction rate was 45%, and the remaining process parameters were the same as in Example 1.

[0081] Comparative Example 3 (Inappropriate Cryogenic Treatment Temperature)

[0082] Except for changing the cryogenic treatment temperature to -80°C, the rest is the same as in Example 1.

[0083] Comparative Example 4 (annealing temperature too high)

[0084] Except for changing the annealing temperature to 920°C, the rest is the same as in Example 1.

[0085] Comparative Example 5 (without internal wall shot peening)

[0086] Except for omitting the nano-surface treatment of the inner wall, the rest is the same as in Example 1.

[0087] Comparative Example 6 (no rotation between passes)

[0088] Except that the pipe does not rotate between adjacent passes (rotation angle is 0°), the rest is the same as in Example 1.

[0089] Comparative Example 7 (Conventional Uniform Cold Rolling)

[0090] Conventional unidirectional cold rolling was used, without inter-pass rotation or deep cryogenic treatment, resulting in a total section reduction of 78%, followed by full annealing at 920°C. The rest is the same as in Example 1.

[0091] Table 1 Comparison of tissue structure parameters between each embodiment and the comparative example

[0092]

[0093] Note: In Comparative Example 4, the nanotwins basically disappeared due to the excessively high annealing temperature, and the twin spacing could not be calculated; in Comparative Example 5, the inner wall was not shot-peened and there was no surface nanocrystalline layer; in Comparative Example 7, the surface was in a conventional fully annealed state without any surface nano-treatment.

[0094] Table 2 Comparison of mechanical properties of each embodiment and comparative example

[0095]

[0096] Table 3 Comparison of key process parameters between each embodiment and the comparative example.

[0097]

[0098] Test data analysis:

[0099] (1) Analysis of the influence of cryogenic treatment on the formation of gradient nanotwin structures:

[0100] Comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the number and timing of cryogenic treatment have a decisive influence on the formation of gradient nanotwin structures. Comparative Example 1 omitted all cryogenic treatments; its nanotwin fractions in the inner wall and middle region were only 18% and 16%, respectively, with an inner-outer wall difference of only 5 percentage points, indicating almost no gradient distribution. The yield strength was only 586 MPa, a 23.1% decrease compared to 762 MPa in Example 1. This shows that while multi-pass rotary cold rolling can introduce some deformation twins, it is insufficient to form a significant nanotwin gradient distribution in the wall thickness direction.

[0101] Comparative Example 2 underwent only one cryogenic treatment, resulting in an inner wall nanotwin fraction of 38%, a middle region fraction of 26%, and an outer wall fraction of 14%, with an inner-outer wall difference of 24 percentage points. This gradient difference was significantly smaller than the 41 percentage points observed in Example 1. The yield strength was 658 MPa, a decrease of 13.6% compared to Example 1. These results indicate that the first cryogenic treatment primarily promotes the refinement of dislocation cells and the compaction of dislocation walls in the inner wall region within the total reduction range of 30%–40%, creating favorable microstructural conditions for subsequent twin nucleation. The second cryogenic treatment further promotes the refinement of twins in the inner wall region and the migration of dislocations to twin boundaries in the outer wall region within the total reduction range of 55%–65%. A synergistic effect exists between the two cryogenic treatments, and neither is dispensable.

[0102] Comparative Example 3 increased the cryogenic treatment temperature to -80°C (higher than the -120°C lower limit specified in this invention). Its inner wall nanotwin integral was only 28%, the inner-outer wall difference was 16 percentage points, and the yield strength was 612 MPa. Compared to Example 1, the yield strength decreased by 19.7%, and the gradient difference decreased by 61%. This result indicates that the cryogenic treatment temperature must be sufficiently low (≤-120°C) to generate a sufficient thermal stress gradient in the pipe wall thickness direction, thereby effectively promoting the evolution of dislocation structures and the formation of nanotwins in the inner wall region. When the cryogenic temperature is insufficient, the thermal stress gradient is small, the promoting effect on dislocation structure evolution is limited, and the gradient distribution of nanotwins is difficult to form.

[0103] (2) Analysis of the influence of inter-pass rotation on gradient structure formation:

[0104] Comparing Example 1 and Comparative Example 6, it can be seen that rotation between passes is a necessary condition for forming a significant gradient structure. In Comparative Example 6, the pipe does not rotate between adjacent passes (rotation angle is 0°), and its nanotwin integral is 25% on the inner wall, 22% in the middle region, and 18% on the outer wall, with a difference of only 7 percentage points between the inner and outer walls. The nanotwin integral is almost uniformly distributed along the wall thickness direction. The yield strength is 634 MPa, which is 16.8% lower than that of Example 1.

[0105] This result can be explained by a strain accumulation mechanism. In conventional unidirectional cold rolling, the stress state of the tube during each rolling pass is basically consistent along the circumference, and the difference in accumulated strain between different regions in the wall thickness direction is small. When the tube rotates 90° between passes, the superposition of the shear strain generated in a specific direction in the previous pass and the strain generated in the same direction in the next pass changes, resulting in differences in strain accumulation between different regions in the wall thickness direction. Specifically, the inner wall region, due to its larger curvature, experiences a higher degree of shear strain reorientation after rotation, resulting in a larger accumulated strain; the outer wall region, with its smaller curvature, experiences a lower degree of strain reorientation, resulting in a relatively smaller accumulated strain. This periodic strain reorientation promotes the accumulation of strain gradients in the wall thickness direction, laying the strain foundation for the formation of nanotwin gradients during subsequent cryogenic treatment and annealing.

[0106] (3) Analysis of the effect of annealing temperature on the stability of gradient nanotwin structure:

[0107] Comparing Example 1 and Comparative Example 4, it can be seen that controlling the annealing temperature is crucial for preserving the gradient nanotwin structure. In Comparative Example 4, the annealing temperature was increased to 920°C (higher than the 850°C upper limit specified in this invention), and the nanotwin integrals of the inner wall, middle region, and outer wall all decreased to below 2%, essentially eliminating the nanotwin structure. The yield strength dropped sharply to 398 MPa, and although the elongation increased to 28.5%, the strength-ductility product was only 11343 MPa·%, lower than the 16231 MPa·% of Example 1.

[0108] This result indicates that the annealing temperature must be controlled within the range of 780–850°C. This temperature range is lower than the complete recrystallization temperature of conventional austenitic stainless steel, but higher than the critical temperature required for nanotwin nucleation. Within this temperature range, the deformation energy stored in the cold-rolled microstructure drives the recovery and partial recrystallization processes, but does not lead to complete grain coarsening. The inner wall region has the highest stored energy, preferentially resulting in nanotwin nucleation and growth; the middle region has the next highest stored energy; and the outer wall region has the lowest stored energy. This creates a gradient distribution of nanotwin integrals. When the annealing temperature exceeds 850°C, complete recrystallization causes the nanotwin structure to disappear, and the gradient structure is destroyed.

[0109] (4) Analysis of the impact of nano-surface treatment on the inner wall:

[0110] Comparing Example 1 and Comparative Example 5, it can be seen that shot peening of the inner wall clearly contributes to the overall performance of the pipe. Comparative Example 5 omitted the nano-sizing treatment of the inner wall surface; its inner wall nanotwin fraction was 51%, which is basically equivalent to 52% in Example 1, indicating that shot peening has a relatively small impact on the nanotwin gradient distribution. However, the inner wall surface hardness was 3.52 GPa, significantly lower than 4.85 GPa in Example 1, a decrease of 27.4%. The yield strength was 694 MPa, a decrease of 8.9% compared to Example 1.

[0111] This result indicates that the main function of shot peening on the inner wall is to form a nanocrystalline structure on the inner wall surface, creating a continuous gradient from nanocrystalline to nanotwins and then to a low dislocation density structure between the nanocrystalline layer and the adjacent nanotwin gradient layer. Under internal compressive loads, this continuous gradient structure provides high strength from the nanocrystalline layer and good strain hardening capability from the nanotwin layer, while the continuous transition between the two avoids stress concentration at the interface. Furthermore, the residual compressive stress introduced by shot peening also helps improve the fatigue performance of the pipe.

[0112] (5) Comprehensive performance comparison analysis:

[0113] Comparing the various embodiments with Comparative Example 7 (conventional uniform cold rolling + fully annealed state) makes the technical effects of the present invention clearer. Comparative Example 7 has a yield strength of only 285 MPa, an elongation of 42.0%, and a strength-ductility product of 11970 MPa·%. Example 1 has a yield strength of 762 MPa, an increase of 167.4% compared to Comparative Example 7; its elongation is 21.3%, lower than Comparative Example 7, but still at a relatively high level above 18%; and its strength-ductility product is 16231 MPa·%, an increase of 35.6% compared to Comparative Example 7. This comparison fully demonstrates that the present invention, by constructing a gradient nanotwin structure, achieves a significant increase in strength while maintaining good ductility, realizing a synergistic optimization of strength and ductility.

[0114] As can be seen from the data in Tables 1 and 2, among the various embodiments, Example 3 exhibits the highest yield strength (812 MPa), the largest integral of nanotwins on the inner wall (61%), and the largest difference between the inner and outer walls (47 percentage points), but its elongation is relatively low (18.9%). Example 4 exhibits the lowest yield strength (685 MPa), the highest elongation (24.8%), and the smallest difference between the inner and outer walls (39 percentage points). This indicates that by adjusting the process parameters, the strength-plasticity matching relationship of the pipe can be controlled within a certain range to meet the needs of different working conditions. For example, for working conditions where pressure bearing is the primary concern and plasticity requirements are relatively low, the process parameters of Example 3 can be selected; for working conditions that require both pressure bearing and formability, the process parameters of Example 4 can be selected.

[0115] As can be seen from the comparison of process parameters in Table 3, the key process parameters of each embodiment of the present invention fall within the range defined by the present invention. However, Comparative Examples 1 to 7 deviate from the technical solution of the present invention in terms of the number of cryogenic treatments, cryogenic temperature, annealing temperature, inner wall shot peening, and rotation angle between passes. A systematic comparison of the test data shows that these deviations all lead to imperfections in the gradient nanotwin structure or a decrease in mechanical properties, further confirming the synergistic effect and irreplaceability of the various process parameters in the technical solution of the present invention.

[0116] In summary, the manufacturing process of this invention, through the synergistic effect of multi-pass rotary cold rolling and programmable intermittent cryogenic treatment, constructs a structure with a continuous gradient distribution of nanotwin integral numbers in the pipe wall thickness direction. Furthermore, gradient annealing and nano-sizing of the inner wall surface further optimize the overall performance. The resulting pipe exhibits a yield strength of 680–850 MPa, an elongation of 18%–25%, and a strength-ductility product of 15347–16990 MPa·%, significantly superior to existing technologies.

[0117] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A seamless stainless steel tube with a gradient nanotwin structure and its manufacturing process, characterized in that, Includes the following steps, S1. Provide a solution-treated austenitic stainless steel seamless tube blank, wherein the tube blank has a wall thickness of 3.0~6.0mm, an outer diameter of 20~40mm, and its chemical composition by weight percentage is: C≤0.03%, Si≤1.0%, Mn8.0-12.0%, P≤0.045%, S≤0.030%, Cr16.0~19.0%, Ni6.0~9.0%, N0.15~0.35%, with the balance being Fe and unavoidable impurities; S2. The tube blank is subjected to multi-pass cold rolling, with a cross-sectional reduction rate of 12% to 18% per pass. The tube is rotated 80° to 100° around its axis between adjacent passes, and the total cross-sectional reduction rate is 70% to 85%. S3. During the multi-pass cold rolling process, when the total section reduction rate reaches 30%~40%, the first deep cryogenic treatment is performed, and when the total section reduction rate reaches 55%~65%, the second deep cryogenic treatment is performed. The temperature of each deep cryogenic treatment is -120°C to -160°C. S4. The pipe obtained in step S3 is annealed in a nitrogen-argon mixed atmosphere at a temperature of 780-850°C. The nitrogen content in the mixed atmosphere is 15%-25%, and the total pressure in the furnace is 0.15-0.25 MPa. S5. Perform surface nano-treatment on the inner wall of the annealed pipe. The surface nano-treatment is rotary shot peening, the shot peening medium is zirconia ceramic shot with a diameter of 0.1~0.3mm, and the peening pressure is 0.3~0.5MPa.

2. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, The multi-pass cold rolling in step S2 uses a three-roll planetary rolling mill with a rolling speed of 30~60mm / s.

3. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 2, characterized in that, The surface roughness Ra of the rolls in the three-roll planetary rolling mill is ≤0.4μm.

4. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, In step S3, each cryogenic treatment process involves cooling to the cryogenic treatment temperature at a rate of 5-10°C / min, holding at that temperature for 30-60 minutes, and then warming back to room temperature at a rate of 2-5°C / min.

5. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, In step S3, the cryogenic treatment is carried out in a liquid nitrogen vaporization atmosphere.

6. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, In step S4, the holding time for the annealing treatment is 10-30 minutes, and the cooling rate is 20-30°C / min.

7. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, In step S5, the rotation speed of the pipe in the rotary shot peening is 200~400 rpm, and the shot peening time is 3~8 minutes.

8. The seamless stainless steel tube with a gradient nanotwin structure and its preparation process according to claim 1, characterized in that, Step S5 is followed by steps of straightening and electropolishing the tube.

9. A seamless stainless steel tube with a gradient nanotwinned structure prepared by the preparation process described in any one of claims 1 to 8, characterized in that, Along the pipe wall thickness direction from the inner wall to the outer wall, the integral number of nanotwins decreases in a gradient: 45%~65% in the inner wall region, 20%~40% in the middle region, and 5%~15% in the outer wall region.

10. A seamless stainless steel tube with a gradient nanotwin structure according to claim 9, characterized in that, The pipe has a yield strength of 680~850MPa, an elongation of 18%~25%, and a grain size of 20~80nm in the inner wall surface layer depth range of 0~50μm.